The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1515/geochr-2015-0064
|View full text |Cite
|
Sign up to set email alerts
|

Variations of tree ring width and chemical composition of wood of pine growing in the area nearby chemical factories

Abstract: This study reports the variation of tree-ring widths and annual variation of concentration of metals (Na, Mg, Fe, Ni, Cu, Zn, Pb) in pine growing nearby chemical factories. The conifers (Pinus silvestris L.) investigated in this study covered the time span from 1920s to 2010 AD. Tree-ring widths were measured, dated and rechecked using the COFECHA. Radial trace-element profiles were determined by Laser Ablation Inductively Coupled Plasma Mass Spectrometry. The combined usage of tree ring width and chemical com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
25
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 67 publications
6
25
0
5
Order By: Relevance
“…This study showed that Pinus sp. (coniferous tree) reflected Pb and Cd concentrations in the atmosphere more effectively than the other elements measured, as confirmed by other studies [5,[28][29][30].…”
Section: Metal Concentration In the Tree Speciessupporting
confidence: 86%
“…This study showed that Pinus sp. (coniferous tree) reflected Pb and Cd concentrations in the atmosphere more effectively than the other elements measured, as confirmed by other studies [5,[28][29][30].…”
Section: Metal Concentration In the Tree Speciessupporting
confidence: 86%
“…Trees from temperate and boreal regions usually form visible annual growth rings that can be dated accurately. Hence, it is possible to collect wood samples of different ages to analyse the elemental composition of the tree rings (Nabais et al 1999, Sensula et al 2017. This method is known as dendrochemistry, i.e., the chronological analysis of elements in the annual growth rings of wood (Nabais et al 1999, Scharnweber et al 2016, Sensula et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is possible to collect wood samples of different ages to analyse the elemental composition of the tree rings (Nabais et al 1999, Sensula et al 2017. This method is known as dendrochemistry, i.e., the chronological analysis of elements in the annual growth rings of wood (Nabais et al 1999, Scharnweber et al 2016, Sensula et al 2017). An important assumption in dendrochemistry is that the elemental concentrations in a given growth ring are the result of environmental conditions at the time of wood formation (Berger et al 2004, Vaganov et al 2013, Maillard et al 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(первые работы [1,2]). На данный момент существует большое количество исследований, связанных с наблюдением изменения тяжелых металлов, микроэлементов и макроэлементов [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], стабильных изотопов и радиоуглерода в древесных кольцах [18][19][20].…”
unclassified